Retropupillary Iris-Claw Intraocular Lenses: A Literature Review - Thulasidas M (Dove Medical Press, 2021)
Mithun Thulasidas Cataract and Glaucoma services, Sankara Eye Hospital, Coimbatore, Tamil Nadu, 641035, IndiaCorrespondence: Mithun ThulasidasCataract and Glaucoma services, Sankara Eye Hospital, Sathy Road, Sivanandapuram, Coimbatore, Tamil Nadu, 641035, IndiaEmail mithun.thulasidas@gmail.comAbstract: Retropupillary iris-claw intraocular lenses (ICIOLs) have been increasingly chosen by surgeons nowadays as a primary or secondary procedure of IOL implantation in eyes with insufficient capsular or zonular support. They have gained popularity due to their simple fast technique, favourable functional outcomes, and safety. The transition in the ICIOL fixation from prepupillary to a more biologically appropriate retropupillary position and change in the optic design from biconvex to convex–concave have provided better visual outcomes and improved safety. A peer-reviewed literature search was conducted in Medline (PubMed), Embase, and Cochrane Library using the keywords “retropupillary iris claw” and “iris claw”. The search yielded 310 articles that were screened. Forty-three articles on retropupillary ICIOLs were finally found to be relevant and reviewed in full-text versions. The functional outcomes following retropupillary implantation of ICIOLs have been acceptable in eyes with no ocular co-morbidities otherwise. However, the indications for surgery may affect the outcomes. The major postoperative complications directly associated with ICIOLs include pupil ovalization and redislocation. Nevertheless, the rate of disenclavation depends on the experience and skill of the surgeon. This review is based on a literature review, and it focuses on the preoperative evaluation, surgical technique, postoperative outcomes, and associated complications. Prospective randomized trials with a larger sample size and longer follow-up are needed for comparison with other techniques of IOL fixation and confirmation of long-term safety profile.Keywords: iris-claw, retropupillary iris-claw, posterior iris-claw, IOL dislocation